Food web of the intertidal rocky shore of the west Portuguese coast – Determined by stable isotope analysis - Vinagre, Catarina (2020)
The characterization of food web structure, energy pathways and trophic linkages is essential for the understanding of ecosystem functioning. Isotopic analysis was performed on food web components of the rocky intertidal ecosystem in four sites along the Portuguese west coast. The aim was to 1) determine the general food web structure, 2) estimate the trophic level of the dominant organisms and 3) track the incorporation of organic carbon of different origins in the diet of the top consumers. In this food web, fish are top consumers, followed by shrimp. Anemones and gastropods are intermediate consumers, while bivalves and zooplankton are primary consumers. Macroalgae Bifurcaria bifurcata, Ulva lactuca, Fucus vesiculosus, Codium sp. and phytoplankton are the dominant producers. Two energy pathways were identified, pelagic and benthic. Reliance on the benthic energy pathway was high for many of the consumers but not as high as previously observed in subtidal coastal food webs. The maximum TL was 3.3, which is indicative of a relatively short food web. It is argued that the diet of top consumers relies directly on low levels of the food web to a considerable extent, instead of on intermediate levels, which shortens the trophic length of the food web.